2015
DOI: 10.1002/cssc.201500288
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Absorption Rate of CO2 in Nonaqueous CO2‐Binding Organic Liquid Solvents with a Wetted‐Wall Apparatus

Abstract: The kinetics of the absorption of CO2 into two nonaqueous CO2-binding organic liquid (CO2 BOL) solvents were measured at T=35, 45, and 55 °C with a wetted-wall column. Selected CO2 loadings were run with a so-called "first-generation" CO2 BOL, comprising an independent base and alcohol, and a "second-generation" CO2 BOL, in which the base and alcohol were conjoined. Liquid-film mass-transfer coefficient (k'g ) values for both solvents were measured to be comparable to values for monoethanolamine and piperazine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
78
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 47 publications
(84 citation statements)
references
References 28 publications
(65 reference statements)
6
78
0
Order By: Relevance
“…testing were performed for both thermal-and polarity-swingassisted regeneration (PSAR) CO 2 release modes. [10] This study revealed that 1-IPADM-2-BOL has the potentialt ob ea ne nergetically viable CO 2 -capture solvent, assuming viscosities could be reduced.…”
mentioning
confidence: 79%
See 4 more Smart Citations
“…testing were performed for both thermal-and polarity-swingassisted regeneration (PSAR) CO 2 release modes. [10] This study revealed that 1-IPADM-2-BOL has the potentialt ob ea ne nergetically viable CO 2 -capture solvent, assuming viscosities could be reduced.…”
mentioning
confidence: 79%
“…The liquid sample was regenerated in situ by raising the water bath temperature to 60°C‐80 °C and reducing the cell pressure using a vacuum pump (Edwards RV8). The operation of the cell was validated using a CO 2 BOL solvent with published viscosity and vapo–liquid equilibrium data …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations